Coilin Affects the Prognosis of Hepatocellular Carcinoma Through Cell Cycle and Apoptosis - Lu L; Zhou X; Zheng J; Li D (Journal of Hepatocellular Carcinoma)
Lingling Lu,1,2,* Xiaoling Zhou,2,3,* Jiaolong Zheng,2,3,* Dongliang Li2,3 1Department of Infection Disease, Fujian Medical University Union Hospital, Fuzhou, People’s Republic of China; 2Fuzong Clinical Medical College of Fujian Medical University, Fuzhou, People’s Republic of China; 3Department of Hepatobiliary Disease, The 900th Hospital of Joint Logistic Support Force, PLA, Fuzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dongliang Li, Email ldliang900@163.com; Lingling Lu, Email 384130051@qq.comPurpose: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality with a challenging prognosis. HCC lacks effective prognostic biomarkers. We investigated the diagnostic and prognostic value of COIL expression in HCC.Patients and Methods: This study evaluated the expression and prognostic significance of COIL using data from the TCGA and local hospital samples, with 374 and 118 liver cancer patients in the TCGA database and local hospital, respectively. The techniques include bioinformatics analysis, qRT-PCR, immunohistochemistry (IHC), and in vitro cell experiments, which encompass CCK-8 assays, wound healing assays, and Transwell invasion assays. The relationship between COIL expression and clinical outcomes was assessed, and COIL’s biological function in HCC was investigated through cellular assays.Results: Analysis of cell lines and HCC tissue samples revealed that COIL mRNA or protein expression levels were significantly higher in HCC cell lines/tissues compared to normal liver cells/tissues. Univariate and multivariate analyses indicated that COIL is an independent prognostic factor for overall survival (OS) in HCC. Additionally, 14% of HCC patients had alterations in the COIL gene, and patients with COIL gene alterations had significantly lower OS (p< 0.001) and disease-free survival (DFS) (p< 0.001) compared to those without gene alterations. Knockdown of COIL expression inhibited the proliferation, migration, and invasion of Hep3B, HepG2, and Huh7. Compared to the control group, COIL knockdown cells showed a marked reduction in CDC25C and CCNB1 protein levels, suggesting that COIL knockdown leads to G2/M phase cell cycle arrest. After COIL knockdown, caspase-3 and BCL-2 protein levels were downregulated, while cleaved caspase and BAX protein levels were upregulated, indicating that COIL knockdown promotes apoptosis in liver cancer cells.Conclusion: COIL is an independent predictor of prognosis. COIL’s association with poor OS and its role in enhancing cancer cell proliferation and invasion highlight its potential as a therapeutic target.Keywords: hepatocellular carcinoma, COIL, prognosis, overall survival